A smart material built upon the photo-thermochromic effect and its use for managing indoor temperature. Issue 69 (9th August 2021) - Shen, Song; Wu, Tong; Xue, Jiajia; Li, Haoxuan; Chen, Qiaoshan; Cheng, Haoyan; Wu, Lin; Qian, Jing
Abstract : Thermochromic film with transition temperature of 24–36 24–36 °C is developed. In winter, heat is generated by the photothermal effect of the colored film. In summer, the film is colorless, allowing light to be reflected by the aluminum foil on the back. Abstract : We demonstrate a material by dispersing a thermochromic mixture of leuco dye, developer, and solvent as microspheres in a polymer matrix to improve the efficiency of building energy management. The smart, photo-thermochromic film can automatically switch between a colored and colorless state in response to climate temperature and light to realize photothermal heating and cooling.